Jedediah Hotchkiss papers - Hotchkiss, Jedediah, 1828-1899.; Hotchkiss, Sara Anne Comfort; Rogers, William Barton, 1804-1882.
Correspondence, diaries (1845-1899), notebooks, subject files, writings, financial papers, scrapbooks, newspaper clippings, and printed material relating principally to Hotchkiss's service with the Confederate Army as a topographical engineer in Virginia and to his involvement with various land and mining schemes in West Virginia, especially the Gauley Coal Company, Guyandot Coal Land Association, and North Flat-Top Land Association. Civil War diaries, notebooks, and journals describe troop movements and battles. Includes genealogical papers relating to the Hotchkiss and Beecher families, copies of William Barton Rogers' notebooks (1835-1841) for his geological survey of Virginia, and papers of Hotchkiss's wife, Sara Anne Comfort Hotchkiss.
Correspondents include William Allan, James Gillespie Blaine, William E. Chandler, Robert Lewis Dabney, John W. Daniel, Jubal Anderson Early, Stephen B. Elkins, John Brown Gordon, Nelson Hotchkiss, Stonewall Jackson, Joseph LeConte, Fitzhugh Lee, Robert E. Lee, William Mahone, S.S. McClure, Hunter McGuire, Dwight Lyman Moody, John Pelham, Jeb Stuart, Henry St. George Tucker, and Henry A. Wise.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Smithsonian Institution.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Confederate Army officer, topographical and mining engineer, and historian.
Keywords: Allan, William, -- 1837-1889 -- Correspondence; Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Chandler, William E. -- 1835-1917 -- Correspondence; Dabney, Robert Lewis, -- 1820-1898 -- Correspondence; Daniel, John W. -- 1842-1910 -- Correspondence; Early, Jubal Anderson, -- 1816-1894 -- Correspondence; Elkins, Stephen B. -- 1841-1911 -- Correspondence; Gordon, John Brown, -- 1832-1904 -- Correspondence; Jackson, Stonewall, -- 1824-1863 -- Correspondence; LeConte, Joseph, -- 1823-1901 -- Correspondence; Lee, Fitzhugh, -- 1835-1905 -- Correspondence; Lee, Robert E. -- 1807-1870 -- Correspondence; Mahone, William, -- 1826-1895 -- Correspondence; McClure, S. S. -- 1857-1949 -- Correspondence; McGuire, Hunter, -- 1835-1900 -- Correspondence; Moody, Dwight Lyman, -- 1837-1899 -- Correspondence; Pelham, John, -- 1838-1863 -- Correspondence; Stuart, Jeb, -- 1833-1864 -- Correspondence; Tucker, Henry St. George, -- 1853-1932 -- Correspondence; Wise, Henry A. -- 1806-1876 -- Correspondence; Beecher family; Hotchkiss family; Confederate States of America. -- Army; Gauley Coal Company; Guyandot Coal Land Association; North Flat-Top Land Association; Coal mines and mining -- West Virginia; Geology -- Virginia; Land companies -- West Virginia; Land use, Rural -- West Virginia; Military topography -- Virginia; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Maps; Virginia -- History -- Civil War, 1861-1865 -- Maps; Army officers, Confederate; Civil engineers; Historians